2007
DOI: 10.1002/hlca.200790042
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Allyl Alcohols of the Pinane Series and of Their Epoxides in the Presence of Montmorillonite Clay

Abstract: The reactivity of allyl alcohols of the pinane series and of their epoxides in the presence of montmorillonite clay in intra-and intermolecular reactions was studied. Mutual transformations of (+)-trans-pinocarveol ((+)-2) and (À)-myrtenol ((À)-3a) were major reactions of these compounds on askanite-bentonite clay (Schemes 1 and 2). However, the two reactions gave different isomerization products, indicating that the reactivity of the starting alcohol (+)-2 or (À)-3a was different from that of the same compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 24 publications
2
39
1
Order By: Relevance
“…[2][3][4] Recently, 5 we found that the storage of (-)-cis-verbenol epoxide 1 on natural montmorillonite askanite-bentonite clay unexpectedly formed trans-diol 2 with a p-menthane framework as the major product (47%). Hydroxyketone 3, which had been obtained before as the major product of this reaction in the presence of ZnBr 2 , 6 was isolated in minor quantities (5%) (Scheme 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Recently, 5 we found that the storage of (-)-cis-verbenol epoxide 1 on natural montmorillonite askanite-bentonite clay unexpectedly formed trans-diol 2 with a p-menthane framework as the major product (47%). Hydroxyketone 3, which had been obtained before as the major product of this reaction in the presence of ZnBr 2 , 6 was isolated in minor quantities (5%) (Scheme 1).…”
mentioning
confidence: 99%
“…The mechanism suggested led to the formation of cation 7 at the key stage of the process. [a] 20 580 -44 (c 12, CHCl 3 )}, obtained from (-)-verbenone by oxidation with aqueous H 2 O 2 and further reduction with LiAlH 4 according to published procedures, 5,9 was added with stirring to a suspension of K10 clay (30.0 g, Fluka), preliminarily calcinated for 3 h at 120°C, in CH 2 Cl 2 (200 ml). The reaction mixture was stirred for 1 h at room temperature.…”
mentioning
confidence: 99%
“…The 1 Н NMR spectra of compounds 5 coincided with those given in the literature. 2 Isopropyl alcohol contains no less than 99.8 wt. % of the main substance and no more than 0.05 wt.% of water.…”
Section: Methodsmentioning
confidence: 99%
“…Conversion products of this monoterpenoid are of great interest mainly due to their high biological activity, for example, compound 6 (Scheme 2) which can be obtained from verbenol epoxide 5 using Montmorillonite clays 2,3 demonstrates high antiepileptic 4 and antiparkinsonian 5 activities. Application of a flow technique for transformations of labile terpenoids such as compound 5 helps to avoid the use of acid catalysts and the inevitable difficulties associated with the catalyst separation, and may also improve the rate and selectivity of the transformations 6 .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it was logical to expect that the ratio of the diastereoisomeric products 16a and 16b would be the same, as in the case of 1, but in fact it was not so (16a/16b 7 : 1 from 1 and 20 : 1 from 2). Previously, we have already observed a considerable difference in the reactivity of monoterpenoids in the presence of clay, which depended on whether they were used as substrates or formed in the course of the reaction [17].…”
mentioning
confidence: 98%